L5: Learning for innovation and adaptive management: Coordination Project Project Lead Organization: FANRPAN - Sullivan, Amy; Sibanda, Lindiwe Majele (2010)
The Coordination and Change project of the Limpopo Basin Development Challenge (L5) is designed to help the four BDC projects conduct quality, coherent, and problem oriented research to contribute to beneficial change in the basin. L5 will develop and implement a communication and knowledge management strategy to facilitate integration of the major activities; capture, store and distribute relevant data; and identify and address capacity building needs—both within the BDC team—and among key external stakeholders.